Monitoring cetacean occurrence and variability in ambient sound in Scottish offshore waters - van Geel, Nienke C. F.; Risch, Denise; Benjamins, Steven; Brook, Tom; Culloch, Ross M.; Edwards, Ewan W. J.; Stevens, Connie; Wilson, Ben (Frontiers in Remote Sensing, 2022)
The characterisation of marine soundscapes allows observation of spatiotemporal distribution of vocalising species and human activities, which can inform an assessment of their interactions. Such data are important for monitoring the ecological status of marine habitats. The Scottish Atlantic Frontier is an important habitat for a variety of cetacean species. Historic whaling has heavily impacted several species inhabiting these waters and current comprehensive information about seasonal occurrence and distribution is lacking for all species. This study presents year-round passive acoustic monitoring data from ten sites in this understudied region. The three most offshore sites were examined for baleen whale vocalisations, and four species were regularly detected. Fin whale detections peaked from October to January and were at their lowest during May and June. Humpback whale song was detected as early as January but showed a strong seasonal peak in March and April. In contrast, minke whales were detected regularly throughout the year but with a peak in detections from October to November, when sei whales were also detected. All monitoring sites showed frequent occurrence of odontocete echolocation clicks and whistles. Comprised mainly of delphinid vocalisations, whistles and clicks were detected on an almost-daily basis among the offshore sites, with a slight reduction in detections from May to July particularly among the more inshore sites. Ambient sound levels (root-mean-square sounds pressure level; SPL) varied by site and season in relation to species presence, anthropogenic contributions, and environmental conditions. Monthly median SPL across the array varied up to 18 dB within 1/3-octave bands. Throughout the year, variability in median SPL was lowest in the higher frequency bands (>10 kHz), while highest variability was found between January to July in specific lower frequency bands (<1 kHz). Results from this study demonstrate the value of passive acoustic data in providing novel baseline information about cetacean occurrence and distribution in Scottish offshore habitats where data are limited and outdated. The results will feed into statutory reporting on underwater noise, support the identification and designation of future marine protected areas for cetaceans, and help guide management of future human-marine mammal interactions in Scottish offshore waters.